Treatment of uncomplicated gonorrhoea with single dose aztreonam. - Evans, D T (1986)
Infection with Neisseria gonorrhoeae was cleared in 61 men and 26 women at all sites (except in the pharynx of one male bisexual patient with urethral and pharyngeal gonorrhoea) after treatment with aztreonam as a single 1 g intramuscular injection. Aztreonam was well tolerated with no adverse effects. This monobactam antibiotic was effective against both penicillin sensitive and resistant strains.